Comparative Study Between Kinesiotaping Versus Muscle Energy Technique in Patients with Knee Osteoarthritis: Life Sciences -Physiotherapy - Anam, Tadar; Kalita, Abhijit; Kalita, Ankita; Dutta, Abhijit (International Journal of Life Science and Pharma Research, 2023)
Osteoarthritis (OA) is a chronic progressive degenerative disorder of multifactorial etiology, causing greater disability and clinical symptoms among adults. Our study aim is to compare the effectiveness of kinesio taping with conventional therapy versus muscle energy technique with conventional therapy in subjects with knee osteoarthritis. Moreover, the assessed objectives are knee pain, range of motion, disability, quadriceps strength, and hamstring flexibility. It is a comparative study, where 30 subjects with knee osteoarthritis meeting the inclusion criteria were recruited and randomly divided into Group A (Kinesiotaping with conventional therapy) and Group B (Muscle energy technique with conventional therapy), each group containing 15 subjects. Both groups received the same conventional therapy, five sessions/week for three weeks. GROUP-A received Kinesiotaping 3 sessions/per week for three weeks, and GROUP-B received Muscle energy technique five sessions/per week for three weeks. Outcome parameters were a Visual Analogue Scale(VAS) for pain, a Goniometer for a range of motion, WOMAC (Western Ontario and McMaster Universities Osteoarthritis Index) for pain, Stiffness, and physical dysfunction, Quadriceps strength test for quadriceps strength and Active knee extension test for hamstrings flexibility. Paired t-test and independent t-test were used to analyze both groups’ pre-test and post-results. The study concluded that Group A showed more significant improvement in knee pain (t=3.862, p<0.05), extension range of motion (t=5.983, p<0.05), and hamstrings flexibility (t=5.983, p<0.05) compared to Group B. However, there was no significant difference in improvement among the groups when compared between both groups. Hence, the intervention in Group A was more effective in decreasing pain and increasing knee extension range of motion and hamstrings flexibility in OA knee patients.